2015
DOI: 10.1007/s12147-015-9139-0
|View full text |Cite
|
Sign up to set email alerts
|

From Sunrise to Sunset: Male Out-Migration and Its Effect on Left-Behind Women in the Builsa District of Ghana

Abstract: The practice of adult males moving from rural areas into urban centres is a common phenomenon in Ghana. The result is that there are a series of consequent impacts on areas of origin especially on households and families. Using in-depth interviews, this paper discusses the economic, social, psychological and emotional effects that women experience as a result of the absence of husbands. Some major findings were that women were expected to work on the farms, feed their children and at the same time support thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Other studies have reported that some left-behind husbands take on care-giving and childcare roles with the assistance of other household/family members such as left-behind older children's siblings, other female relatives, maternal and/or paternal grandparents, aunts and uncles, and to a minimal extent, non-family domestic workers in providing care when their wives are away (Hochschild, 2000;Afsar, 2005;Hugo, 2005;Parreñas, 2005;Cortes, 2015;Lam &Yeoh, 2018). In Ghana, the experiences of left-behind husbands whose wives have migrated have not attracted much research compared to the other way round (Wrigley-Asante & Agandin, 2015). In a study on effects of husbands migration on left-behind wives in the Builsa District, it was noted that majority of the leftbehind women in the absence of their husbands cultivated small portions of land due to the absence of hired labour, which resulted in low productivity, and also that they became defected household heads in charge of various household responsibilities but limited in their decision making roles (Wrigley-Asante & Agandin, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have reported that some left-behind husbands take on care-giving and childcare roles with the assistance of other household/family members such as left-behind older children's siblings, other female relatives, maternal and/or paternal grandparents, aunts and uncles, and to a minimal extent, non-family domestic workers in providing care when their wives are away (Hochschild, 2000;Afsar, 2005;Hugo, 2005;Parreñas, 2005;Cortes, 2015;Lam &Yeoh, 2018). In Ghana, the experiences of left-behind husbands whose wives have migrated have not attracted much research compared to the other way round (Wrigley-Asante & Agandin, 2015). In a study on effects of husbands migration on left-behind wives in the Builsa District, it was noted that majority of the leftbehind women in the absence of their husbands cultivated small portions of land due to the absence of hired labour, which resulted in low productivity, and also that they became defected household heads in charge of various household responsibilities but limited in their decision making roles (Wrigley-Asante & Agandin, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In Ghana, the experiences of left-behind husbands whose wives have migrated have not attracted much research compared to the other way round (Wrigley-Asante & Agandin, 2015). In a study on effects of husbands migration on left-behind wives in the Builsa District, it was noted that majority of the leftbehind women in the absence of their husbands cultivated small portions of land due to the absence of hired labour, which resulted in low productivity, and also that they became defected household heads in charge of various household responsibilities but limited in their decision making roles (Wrigley-Asante & Agandin, 2015). The authors further established that some of the women were already experiencing psychological stresses owing to the burden of taking care of children, farming, maintenance of building, loneliness, the feeling of insecurity and uncertainty in the absence of their husbands (Wrigley-Asante & Agandin, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation